2015
DOI: 10.1111/jnc.13060
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular α‐synuclein alters synaptic transmission in brain neurons by perforating the neuronal plasma membrane

Abstract: It has been postulated that the accumulation of extracellular asynuclein (a-syn) might alter the neuronal membrane by formation of 'pore-like structures' that will lead to alterations in ionic homeostasis. However, this has never been demonstrated to occur in brain neuronal plasma membranes. In this study, we show that a-syn oligomers rapidly associate with hippocampal membranes in a punctate fashion, resulting in increased membrane conductance (5 fold over control) and the influx of both calcium and a fluores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
78
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(84 citation statements)
references
References 39 publications
5
78
1
Order By: Relevance
“…Moreover, membrane leakage and subsequent dysregulation of calcium signaling may underlie synaptic transmission deficits seen in similar models (Pacheco et al . ). Recently, the fragmentation of lipid rafts was also reported following the application of exogenous α‐Syn aggregations, which may further contribute to alterations in synaptic physiology via the modulation of pre‐synaptic Ca 2+ transients and the disruption of post‐synaptic receptor clustering (Emanuele et al .…”
Section: Cell Models Based On the Treatment With Exogenous α‐Syn Speciesmentioning
confidence: 97%
“…Moreover, membrane leakage and subsequent dysregulation of calcium signaling may underlie synaptic transmission deficits seen in similar models (Pacheco et al . ). Recently, the fragmentation of lipid rafts was also reported following the application of exogenous α‐Syn aggregations, which may further contribute to alterations in synaptic physiology via the modulation of pre‐synaptic Ca 2+ transients and the disruption of post‐synaptic receptor clustering (Emanuele et al .…”
Section: Cell Models Based On the Treatment With Exogenous α‐Syn Speciesmentioning
confidence: 97%
“…Our data are in line with recent studies showing that interaction and aggregation of α-syn with lipid bilayers or vesicles in vitro leads to membrane disintegration 52,57 and in vivo accumulation of extracellular α-syn at the surface of primary neurons perforates the plasma membrane leading to synaptic transmission defects and neuronal cell loss. 58 Interestingly, newly formed α-syn aggregates following the addition of α-syn mixture to the culture media were internalized into M17 cells more rapidly than pure PFFs. These findings, combined with our CLEM data, suggest that the process of aggregation at the plasma membrane led to modifications and/ or partial disruption of the cell membrane, which in turn facilitates the internalization of α-syn fibrils, newly formed aggregates or even the uptake of α-syn monomers present in excess in the cell culture media.…”
Section: F(2 μM) M(18μm) + F(2μm)mentioning
confidence: 99%
“…However, we cannot rule out other modifications. A potential mechanism by which phosphorylated α -syn oligomers induce cell death is by directly damaging the plasma membrane, thereby increasing membrane permeability via formation of amyloid pores [30, 40]. As previously summarized, oligomerization of α -syn is the first step that leads to subsequent formation of amyloid-like fibrils [38].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, both α -syn monomers and oligomers are released from neurons [28] and are present in extracellular fluids, including cerebrospinal fluid and blood plasma [29]. In vitro and in vivo experiments have shown that these molecules are internalized by neurons via endocytosis or translocation across the plasma membrane [30]. Some types of α -syn oligomers can be induced to form aggregates [31], suggesting that these species are responsible for the spread of α -syn pathology.…”
Section: Introductionmentioning
confidence: 99%